Skills Information Base for Technical and Vocational Education and Training Policy - Sirohi, Vineeta (INDIAN EDUCATIONAL REVIEW, 2014)
The information and evidence based decision making is imperative, particularly with regard to Technical and Vocational Education and Training (TVET) policy, considering its unique mandate to equip people with knowledge and skills required by the world of work. It is critical that TVET policy be drawn from a comprehensive information base which is established from the outset in order to inform the framework of TVET system. In India, the skill information base suffers from glaring deficiencies such as inadequacy of data, absence of fixed periodicity of collecting information, absence of effective legislation, incomplete information and nonavailability of micro level/disaggregated information. Besides, the trend of increasing population in the younger age group and falling dependency ratio would need a paradigm shift in the skill development policy and it would be possible to harness the demographic dividend only if the country delivers more informed decision support system and effective policy intervention.